Meandering pastures of memories - Narayan, Shovana (New Delhi, 2007)
Meandering Pastures of Memories is a fascinating tale of determination, achievement, insight and sincerity. The pastures of memories cover activities of Shovana Narayan, the protagonist, which provide a vast, multi-hued and multi-dimensional panorama that has subtly influenced her life and the society as a whole.
Keywords: Shovana Narayan-Biography